O Plantão Psicológico como um possível dispositivo de cuidado em saúde mental no contexto universitário - Pereira, Glauce Alves (Universidade Federal de São Carlos, 2024)
In face of the significant demand for support in the care of psychological suffering in university community and the gaps in the mental health policy for this group, it has been observed the need for Psychology, as an area of mental health, to take care to the context in which these individuals are placed. Objectives: This study aimed to discuss, through a Case Study, the viability of Psychological duty as a resource for mental health care in the university environment. Methodology: This is a Case Study, with a qualitative approach, including the description of the organization, implementation and evolution of a project called Psychological Duty (Plantão Psicológico). Results: The proposal emerged from a specific demand from one of the departments of a federal public university. The psychoanalytic approach was used as a theoretical and practical foundation to structure the physical space, compose the work team and establish opening hours, in addition to analyzing and guiding emerging emotional demands. Data analysis: The data was analyzed using thematic analysis, considering 3 moments: 1. From the proposal to the organization of the duty; this moment was dedicated to the concrete needs for the functioning of the duty, organization of the environment and work team, where the articulation of theory and practice were present, taking into account the ethical guidelines for the functioning of the Psychological Duty. 2. The psychoanalytic technique in Psychological Duty assistance; moment in which the gaze was focused on emotional emergencies, helping the individual to perceive the intensity of emerging emotions and take ownership of the need to find the possibility of coping. 3. Finalization of the Psychological Duty proposal; At a time when the project was confronted with the gaps found in health policies, the needs of the team on duty staff who participated in the project and the project's lack of connection with other mental health care facilities for the university public, affected the project's initial proposal. Conclusions: It was observed that the Psychological Duty, aligned with the purpose of promoting, preventing, and protecting the collective mental health of the involved university community, can be considered a relevant resource for the psychological care of this public. It is worth emphasizing the importance of building a support network alongside other mental health services to ensure longitudinal care.
Psychological Duty as a possible device for mental healt care in the university context
Keywords: Plantão psicológico; Universidade; Psicanálise; Saúde mental; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO::DESENVOLVIMENTO SOCIAL E DA PERSONALIDADE